CHALLENGES OF MANAGING LOCAL SELF-GOVERNMENT - Budimirović, Marko (International Journal of Economic Practice and Policy, 2017)
Local self-governments have often been criticized by public for being ineffective. Both the public sector and local government units have been based on its own specifics, thus efficacy, like in economy, cannot be expected in performing business tasks. Nevertheless, it is necessary to carry out a reform. Proper management is of paramount importance in order to achieve the efficient and effective local self-government. Firstly, it is necessary to perform an analysis of local self-government, and secondly, to establish a model of management, which shall provide efficacy with respect of specifics which public sector is based on, in order to provide effective local self-government which acts in the interests of citizens. This paper shall be based on the analysis of local self-governments.
Keywords: local self-government; city; municipality; management; new public management